Cultivation of Tawadhu (Humility) and Discipline Among Students at Madin - Rahmania, Nurani; Mun'im, Ali; Kh, Humaidi; Mashuri, Imam; Suryantoro, Dwi Dasa (IERA, Islamic Education and Research Academy, 2024)
Character building of students can be achieved by habituating good behaviors in daily life. Habituation is a process of forming consistent attitudes and behaviors through repetitive learning, both individually and collectively. In the context of teaching methods in Islamic education, it can be said that "habituation is a method used to accustom students to think, behave, and act according to the teachings of Islam." This study is a qualitative field research. Data collection was conducted through observation, interviews, and documentation. The object of this research is the cultivation of Tawadhu (humility) and discipline among students at Madin Al-Hikmah, Lengkong District. The findings of this study indicate that the process of cultivating Tawadhu and discipline at Madin Al-Hikmah is implemented as long as the students are enrolled at the institution. The cultivation is carried out through habituation and the exemplary conduct of the teachers. Habituation of Tawadhu includes being humble, not arrogant, speaking politely, greeting others and shaking hands while kissing the teacher's hand, as well as respecting and obeying the teachers' instructions. Meanwhile, the habituation of discipline among students includes arriving on time, dressing neatly, participating in congregational prayers, and completing the tasks assigned by the teachers